Introduction to the human gut microbiota - Thursby, Elizabeth; Juge, Nathalie (Biochemical journal, 2017)
The human gastrointestinal (GI) tract harbours a complex and dynamic population of microorganisms, the gut microbiota, which exert a marked influence on the host during homeostasis and disease. Multiple factors contribute to the establishment of the human gut microbiota during infancy. Diet is considered as one of the main drivers in shaping the gut microbiota across the life time. Intestinal bacteria play a crucial role in maintaining immune and metabolic homeostasis and protecting against pathogens. Altered gut bacterial composition (dysbiosis) has been associated with the pathogenesis of many inflammatory diseases and infections. The interpretation of these studies relies on a better understanding of inter-individual variations, heterogeneity of bacterial communities along and across the GI tract, functional redundancy and the need to distinguish cause from effect in states of dysbiosis. This review summarises our current understanding of the development and composition of the human GI microbiota, and its impact on gut integrity and host health, underlying the need for mechanistic studies focusing on host-microbe interactions.